Learning to be literate : the development of spoken and written language - Garton, Alison F., 1950-; Pratt, Chris (Oxford, UK ; New York, NY : Blackwell, 1989)
Literacy: the spoken and written language. Explanations of spoken language development. Social interaction and the development of language. Learning spoken language...
Keywords: Language; Literacy; Children -- Language; Literacy; Language acquisition; Written communication -- Study and teaching